Identification of disease-specific gut microbial markers in vitiligo - Dou, Yimin; Niu, Yi; Shen, Hexiao; Wang, Lan; Lv, Yongling; Liu, Suwen; Xie, Xiafei; Feng, Aiping; Liu, Xinxin (Frontiers in Microbiology, 2025)
There is a potential correlation between vitiligo and gut microbiota, although research in this area is currently limited. The research employed high-throughput sequencing of 16S rRNA to examine the gut microbiome in the stool samples of 49 individuals with vitiligo and 49 without the condition. The study encompassed four comparison groups: (1) DI (disease) group vs. HC (healthy control) group; (2) DI_m group (disease group of minors) vs. HC_m group (healthy control group of minors); (3) DI_a group (adult disease group) vs. HC_a group (adult healthy control group); (4) DI_m group vs. DI_a group. Research findings have indicated the presence of spatial heterogeneity in the gut microbiota composition between individuals with vitiligo and healthy controls. A significant reduction in gut microbiota diversity has been observed in vitiligo patients across both minors and adult groups. However, variations have been noted in the composition of disease-related differential microbial markers among different age groups. Specifically, Bacteroides and Parabacteroides have been identified as specific markers of the intestinal microbiota of vitiligo patients in both minor and adult groups. Correlative analyses have revealed a positive correlation of these two genera with the Vitiligo Area Scoring Index (VASI) and disease duration. It is noteworthy that there are no significant differences in diversity between the DI_m group and the DI_a group, with similarities in microbiota composition and functional characteristics. Nevertheless, correlative analyses suggest a declining trend in Bacteroides and Parabacteroides with increasing age. Individuals with vitiligo exhibit distinct features in their gut microbiome when contrasted with those in the healthy control group. Additionally, the microbial marker genera that show variances between patients and healthy controls vary among different age groups. Disease-specific microbial marker genera (Bacteroides and Parabacteroides) are associated with VASI, duration of the condition, and age. These findings are essential for improving early diagnosis and developing potential treatment strategies for individuals with vitiligo.